2011
DOI: 10.1002/jqs.1453
|View full text |Cite
|
Sign up to set email alerts
|

Exotic pollen as an indicator of variable atmospheric circulation over the Labrador Sea region during the mid to late Holocene

Abstract: Variability in the abundance of exotic (non-native) pollen in sediment cores has long been considered as a potential proxy for changing atmospheric circulation, but the difficulty of gaining sufficient total exotic pollen and the incomplete understanding of atmospheric pollen transport patterns has hindered its application. In light of recent advances in the study of pollen transport, we present an exotic pollen record from two fjord sediment cores taken from the west (Placentia Bay, Newfoundland) and east (Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 76 publications
4
54
0
Order By: Relevance
“…Reduced Siberian river discharge during the past 2000 years BP and vegetation changes in northeast European Russia, for example, are interpreted to reflect the development of a colder and dryer climate in the Eurasian Arctic and could be related to negative NAO-like conditions (Stein et al, 2004;Salonen et al, 2011). And also Jessen et al (2011) relate changes in Late Holocene pollen records from southern Greenland and the Labrador Sea to a distinct reduction of south-westerly air masses in favour of colder air originating from the north and thus conclude that the atmospheric circulation pattern in the subpolar North Atlantic likely shifted from a more positive to a more negative NAO. Sicre et al (2008) attribute short-term SST changes off North Iceland during the Late Holocene to low frequency NAO forcing that partly seems to be associated with fluctuations in the meridional overturning circulation (Latif et al, 2006) and thus (large-sale) alterations in the Atlantic hydrological cycle.…”
Section: Sea Ice Fluctuations and North Atlantic Oscillationmentioning
confidence: 99%
“…Reduced Siberian river discharge during the past 2000 years BP and vegetation changes in northeast European Russia, for example, are interpreted to reflect the development of a colder and dryer climate in the Eurasian Arctic and could be related to negative NAO-like conditions (Stein et al, 2004;Salonen et al, 2011). And also Jessen et al (2011) relate changes in Late Holocene pollen records from southern Greenland and the Labrador Sea to a distinct reduction of south-westerly air masses in favour of colder air originating from the north and thus conclude that the atmospheric circulation pattern in the subpolar North Atlantic likely shifted from a more positive to a more negative NAO. Sicre et al (2008) attribute short-term SST changes off North Iceland during the Late Holocene to low frequency NAO forcing that partly seems to be associated with fluctuations in the meridional overturning circulation (Latif et al, 2006) and thus (large-sale) alterations in the Atlantic hydrological cycle.…”
Section: Sea Ice Fluctuations and North Atlantic Oscillationmentioning
confidence: 99%
“…pollen, charcoal) but not so close that the influx is constant over time. Whilst numerous studies have been undertaken in the Arctic (Fredskild, 1984;Jessen et al, 2011) and the high latitudes of the Indian and Pacific oceans (McGlone et al, 2000;Scott and van Zinderen Barker, 1985), few have been reported from the South Atlantic. Recent work on a lake core taken from Annekov Island, South Georgia (Strother et al, 2015) demonstrates the considerable potential of this approach but the relatively large distance from the nearest source in South America ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These data therefore suggest that there was potentially an increased availability of Alnus pollen for long-distance transport to southern Greenland during this period. Indeed, a fjord sediment core from southern Greenland does record increased Alnus pollen percentages at this time (Jessen et al 2011). Although these data are far from conclusive, they do hint at the possibility of scattered populations of alder in the Vatnahverfi region.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, it may relate to the increased exposure of the more southerly sites to the westerly track of air masses across the North Atlantic. These air masses, arriving from eastern North America, are responsible for the majority of the precipitation experienced in southern Greenland (Chen et al 1997;Jessen et al 2011) and would have ample opportunity to become enriched in Alnus pollen (e.g. Rousseau et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation